Analysis of Financial Statements Using Solvency Ratios to Assess Financial Stability - Lucia Chandra Dewi; Andi Santoso; Noor Azizah; Totok Adi Prasetyo (Moneter : Jurnal Ekonomi dan Keuangan, 2026)
This study aims to analyze the use of solvency ratios in assessing the financial stability and long-term financial performance of companies. A quantitative descriptive approach was employed using secondary data obtained from the 2024 consolidated financial statements of PT Telkom Indonesia (Persero) Tbk. The analysis focuses on four key solvency indicators: Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), Long-Term Debt to Equity Ratio (LTDER), and Times Interest Earned (TIE). These ratios were selected because they provide comprehensive information regarding a company’s capital structure, debt management, and ability to fulfill long-term financial obligations. The results show that the company recorded a Debt to Asset Ratio of 45.77%, a Debt to Equity Ratio of 84.42%, a Long-Term Debt to Equity Ratio of 37.18%, and a Times Interest Earned ratio of 8.25 times. These findings indicate that PT Telkom Indonesia (Persero) Tbk maintains a relatively healthy capital structure, a well-controlled level of long-term debt, and a strong capacity to meet interest payment obligations through operating income. Therefore, solvency ratio analysis can serve as an effective tool for evaluating financial resilience, supporting strategic business decision-making, and providing valuable insights for investors, creditors, and other stakeholders in assessing the company’s long-term financial sustainability.